2019
DOI: 10.1111/apha.13285
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Role of the immune system in vascular function and blood pressure control induced by faecal microbiota transplantation in rats

Abstract: Aim: High blood pressure (BP) is associated with gut microbiota dysbiosis. The aim of this study was to investigate whether changes in gut microbiota induced by exchanging the gut microbiota between spontaneously hypertensive rats (SHR) and normotensive Wistar-Kyoto (WKY) alter the gut-immune system interaction inducing changes in vascular function and BP. Methods: Twenty-week-old recipient WKY and SHR were orally gavaged with donor faecal contents from WKY or SHR. In additional experiments, we used a design t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
132
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(146 citation statements)
references
References 44 publications
11
132
3
Order By: Relevance
“…In order to determine NADPH oxidase activity, the lucigenin‐enhanced chemiluminescence assay was performed in intact aortic rings, as previously described . We used a colorimetric Nitric Oxide Synthase (NOS) Activity Assay Kit (abcam, Abingdon, UK) to determine NO production in aortic segments from all groups.…”
Section: Methodsmentioning
confidence: 99%
“…In order to determine NADPH oxidase activity, the lucigenin‐enhanced chemiluminescence assay was performed in intact aortic rings, as previously described . We used a colorimetric Nitric Oxide Synthase (NOS) Activity Assay Kit (abcam, Abingdon, UK) to determine NO production in aortic segments from all groups.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has been demonstrated that the normal gut microbiota may influence BP. A direct association between gut microbiota and hypertension in both animal models and humans has been described (Yang et al, ; Kim et al, , Toral et al, , , Sun et al, ). In contrast, Karbach et al () showed that BP was not different between germ‐free and conventionally raised mice, which is consistent with previous observations describing no effect on BP after dramatic reduction in faecal microbial biomass induced by antibiotic treatment (Pluznick et al, ).…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, systolic BP (SBP) positively correlated with six bacterial species ( Parabacteroides johnsonii , Klebsiella unclassified , Anaerotruncus unclassified , Eubacterium siraeum , Prevotella bivia , and Rumminococcus torques ) and negatively correlated with three ( Bacteroides thetaiotaomicron , Paraprevotella clara , and Paraprevotella unclassified ) species (Kim et al, ). In SHR, a strong positive correlation between SBP and the lactate‐producing genus Lactobacillus (Adnan et al, ), or Streptococcus and Turicibacter (Toral et al, ; Yang et al, ), and a negative correlation between butyrate‐producing bacteria genus Odoribacter and acetate‐producing bacteria genus Bautia with SBP (Toral et al, ) have been described. However, the absence of gut microbiota protects mice from angiotensin II‐induced hypertension, vascular dysfunction, and hypertension‐induced end‐organ damage, showing for the first time that commensal microbiota, an ecosystem acquired after birth, could represent an environmental factor promoting angiotensin II‐induced high BP (Karbach et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the hypertensive phenotype was transferred via fecal transplantation into GF mice repeatedly, proving an influence of the gut microbiota on blood pressure [44]. Various approaches suggest that microbiota metabolites interact with receptors in the brain and vascular walls, as well as affecting immune cells and changing blood pressure [45,46].…”
Section: Introductionmentioning
confidence: 99%